2022
DOI: 10.1186/s13040-022-00289-8
|View full text |Cite
|
Sign up to set email alerts
|

PredictPTB: an interpretable preterm birth prediction model using attention-based recurrent neural networks

Abstract: Background Early identification of pregnant women at risk for preterm birth (PTB), a major cause of infant mortality and morbidity, has a significant potential to improve prenatal care. However, we lack effective predictive models which can accurately forecast PTB and complement these predictions with appropriate interpretations for clinicians. In this work, we introduce a clinical prediction model (PredictPTB) which combines variables (medical codes) readily accessible through electronic healt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Compared to previously presented methods for the prediction of PTB, the results in terms of ROC-AUC have been similar. However, we notice an increase of the PR-AUC to ~0.72 compared to other applications [7,8] with the ensemble methods in our models.…”
Section: Discussion and Future Workmentioning
confidence: 52%
See 1 more Smart Citation
“…Compared to previously presented methods for the prediction of PTB, the results in terms of ROC-AUC have been similar. However, we notice an increase of the PR-AUC to ~0.72 compared to other applications [7,8] with the ensemble methods in our models.…”
Section: Discussion and Future Workmentioning
confidence: 52%
“…Taking into account the pregnant woman's medical history, current pregnancy information, and predictive clinical tests, the QUiPP application is able to predict her likelihood of giving PTB within clinically significant timeframes. In another study [7], authors proposed the PredictPTB model, a deep learning model, similarly able to predict PTB using routinely collected data from electronic health records (EHRs). Moreover, an intelligent mechanism based on the SVM algorithm has been introduced [8], capable of predicting PTB among others.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, RETAIN can detect both influential nurse visits and clinical features [16]. Several studies have demonstrated the clinical utility of the RETAIN model in diverse clinical contexts [18][19][20][21][22][23]. AlSaad et al [21] have shown a simplified version of the RETAIN architecture that significantly predicted preterm birth and enabled individual-level prediction explanations at the visitation level and medical code level (International Classification of Diseases, Ninth Revision [ICD-9] or ICD-10 codes).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the clinical utility of the RETAIN model in diverse clinical contexts [18][19][20][21][22][23]. AlSaad et al [21] have shown a simplified version of the RETAIN architecture that significantly predicted preterm birth and enabled individual-level prediction explanations at the visitation level and medical code level (International Classification of Diseases, Ninth Revision [ICD-9] or ICD-10 codes). Rasmy et al [23] have adapted a language model that combined the RETAIN model with two independent EHR databases; this model achieved a high degree of accuracy in predicting both heart failure and the onset of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying mothers that are at a higher risk through quantifying risk factors of preterm delivery at a population level helps clinicians to take preventive measures and mitigate the risks [ 12 , 13 ]. Traditionally, the identification of such risk factors is done through prospective studies.…”
Section: Introductionmentioning
confidence: 99%